On Variant Selection Mechanisms in Interactive MCDA – Engineering versus Reverse Engineering. Issue 1 (11th November 2015) - Kaliszewski, Ignacy
Abstract: In the paper, we focus on the engineering and the reverse engineering paradigms in the context of multiple criteria decision analysis. We argue and demonstrate that if variant selection mechanisms are reverse engineered, they are simple and intuitive to understand, making multiple criteria decision analysis marketable to operational research practitioners. We present a reverse engineering scheme for variant selection mechanisms, and we illustrate its working with instructive examples. We also present some experience with that scheme gathered when teaching a multiple criteria decision analysis course to students. Copyright © 2015 John Wiley & Sons, Ltd.